KORELASI PRESTASI BELAJAR MATA PELAJARAN KEWIRAUSAHAAN DAN PRESTASI PRAKTIK INDUSTRI DENGAN MINATBERWIRAUSAHA SISWA KELAS XII SMK MA’ARIF KOTA MUNGKIDKABUPATEN MAGELANGTAHUN PELAJARAN2014/2015 - Gunawanto Bakti Putro; Slamet Priyanto (Jurnal Taman Vokasi, 2016)
Correlation Learning Achievement Subjects Enterprise and Industry Interests Practice Achievement Entrepreneurship Class XII SMK Ma'Arif Kota Mungkid  Magelang District Academic Year 2014/2015. Thesis Mechanical Engineering Study Program of the Faculty of Education University of Sarjanawiyata Tamansiswa Yogyakarta, 2016.The purpose of this study is (1) To determine the level of correlation learning achievement entrepreneurship subjects with class XIISMK Ma'Arif Kota Mungkid  Magelang District Academic Year 2014/2015. (2) To determine the level of correlation learning achievementindustry practice with interest in entrepreneurship students of class XIISMK Ma'Arif Kota Mungkid  Magelang District Academic Year 2014/2015. (3)To determine the level of correlation learning achievement entrepreneurship subjects and achievements of industry practice with interest in entrepreneurship students of class XIISMK Ma'Arif Kota Mungkid  Magelang District Academic Year 2014/2015.Correlational research type and using a quantitative approach to determine the effect of two variables is how much correlation. This research was conducted at SMK Ma'Arif Kota Mungkid  Magelang District Academic Year 2014/2015with a population of 159 students. The research sample is determined by Isaac and Michael, which amounted to 110 students. The sampling technique is random sampling. The data collection technique using questionnaires (questionnaire) and methods of documentation. The validity of the questionnaire instrument made with grain analysis using Product Moment Correlation formula and reliability test using Cronbach Alpha formula. Testing the hypothesis with regression analysis andpartial correlation analysis, which had previously been carried out analysis prerequisite test including normality test, linearity and multicollinearity